Patterns of cortical activity and memory performance in Alzheimer’s disease - Schröder, Johannes; Buchsbaum, Monte S.; Shihabuddin, Lina; Tang, Cheuk; Wei, Tse-Chung; Spiegel-Cohen, Jacqueline; Hazlett, Erin A; Abel, Lennart; Luu-Hsia, Christina; Ciaravolo, Tina M; Marin, Deborah; Davis, Kenneth L (Biological psychiatry, 2001)
Background: %Declarative memory changes are the hallmark of Alzheimer’s disease, although their functional neuroanatomy is not restricted to a single structure. Factor analysis provides statistical methods for evaluating patterns of cerebral changes in regional glucose uptake. Methods:Thirty-three Alzheimer’s patients and 33 age- and gender-matched control subjects were studied with magnetic resonance imaging and positron emission tomography with [18F] deoxyglucose. During the tracer-uptake period, subjects performed a serial verbal learning task. Cortical activity was measured in 32 regions of interest, four in each lobe on both hemispheres. Results:Factor analysis with varimax rotation identified seven factors explaining 80% of the variance (“parietal cortex,” “occipital cortex,” “right temporo-prefrontal areas,” “frontal cortex,” “motor strip,” “left temporal cortex,” and “posterior temporal cortex”). Relative to control subjects, Alzheimer’s patients showed significantly reduced values on the factors occipital cortex, right temporo-prefrontal areas, frontal cortex, and left temporal cortex. The factor temporo-prefrontal areas showed large differences between patients with good and poor performance, but little difference when control subjects were similarly divided. Conclusions:Findings suggest that Alzheimer’s disease is characterized by altered patterns of cortical activity, rather than deficits in a single location, and emphasize the importance of right temporo-prefrontal circuitry for understanding memory deficits.